Recycling of plastics, metals, and their composites - Ilyas, Rushdan Ahmad; Sapuan, S. M.; Bayraktar, Emin (Boca Raton, FL : CRC Press, 2022)
'This authoritative reference work provides a comprehensive review of the recycling of waste polymer and metal composites. It provides readers with the latest advances and covers fundamentals of recycled polymer and metal composites such as preparation, morphology, and physical, mechanical, thermal, and flame-retardancy properties. This work targets technical professionals working in the metal and polymer industries, as well as researchers, scientists, and advanced students. It is also of interest to decision makers at material suppliers, recycled metal and polymer product manufacturers, and governmental agencies working with recycled metal and polymer composites'--
Includes bibliographical references and index.
Keywords: Recycling (Waste, etc.).